2003
DOI: 10.1097/00003226-200307000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Changes in Magnesium-Deficient Rats

Abstract: Since Mg2+ has biologic functions including structural stabilization of protein, nucleic acids, and cell membranes, Mg deficiency may induce changes in the corneal surface and nuclei of corneal epithelial and endothelial cells. These disturbances may interfere with protection from infections, foreign bodies, dryness, and direct exposure to air. Thus, Mg is essential for the cornea to maintain normal structure and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A series of studies on Zn [14], Mg [16] and Mn [15] deficiencies showed some corneal changes similar to those seen in riboflavin deficiency. The deficiency of these essential trace elements may lead to cell degeneration as well as lowered activity of the superoxide dismutases (SOD) Zn W Cu-SOD and Mn-SOD [20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A series of studies on Zn [14], Mg [16] and Mn [15] deficiencies showed some corneal changes similar to those seen in riboflavin deficiency. The deficiency of these essential trace elements may lead to cell degeneration as well as lowered activity of the superoxide dismutases (SOD) Zn W Cu-SOD and Mn-SOD [20].…”
Section: Discussionmentioning
confidence: 93%
“…Abnormal secretion in riboflavin deficiency may be one of these disturbances. On the other hand, the changes in the cornea are specific for riboflavin deficiency and not seen in other micronutrient deficiencies such as those of Zn [14], Mn [15], Mg [16], Cr, and vitamins A [17] and C. The reduction of microvilli and microplicae in the corneal surface is common in those micronutrient deficiencies, but only riboflavin deficiency induces degenerative changes of the wing cells, onion-shaped dense deposits in the subepithelial area, and degenerative stroma cells. The significance of dense deposits in the subepithelial stroma is unclear, but we assume that degeneratedwing cells are released to the subepithelial stroma through basal cells and dense deposits represent cellular debris, because epithelial cells generally release waste products from the basal portion like the dense deposits in Bruch's membrane [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Trace elements deficiency, undernourishment, and exposure to drugs of abuse or alcohol induced ultrastructural changes in the ON, cornea, and retina. 25,26,29,[31][32][33][34][35][42][43][44][45][46][47][48][49][50][51][52][53] Figure 2 Mean density (a) and total number (b) of myelinated and unmyelinated fibres of the optic nerve in the control, anaemic, and recovered rats at postnatal day 32. Values are means ± SE for n ¼ 6; *Po0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium also may be necessary for maintenance of corneal surface health which is important for protection from infections and dryness. Cornea has showed some structural changes if magnesium is missing in the developmental cycle, including decreased microvilli in the epithelial cells, nuclear changes like apoptosis in the epithelial and endothelial cells through abnormal ATP activity and abnormal ion transport [37].…”
Section: Necessity In Terms Of Eye Tissue Developmentmentioning
confidence: 99%